The Role of Beauty in Physics - Melo, Ivan (Communications - Scientific letters of the University of Zilina, 2018)
The goal of physics is to look for the truth behind the physical phenomena. Where is the place for the beauty then? The truth can be in principle ugly in one case and aesthetically pleasing in another. Nevertheless, many physical theories can be considered as beautiful and are often formulated with aesthetic criteria in mind. These criteria include the ability to explain a lot starting from a little and/or some form of symmetry. Several examples of beautiful laws will be discussed along with opinions of particle physicists on beauty.